An Efficient Oxidation of Sulfides to Sulfones with Urea–Hydrogen Peroxide in the Presence of Phthalic Anhydride in Ethyl Acetate - Lutz, Marlon; Wenzler, Marta; Likhotvorik, Igor (Synthesis, 2018)
A metal-free, environmentally benign oxidation of substituted sulfides directly to their corresponding sulfones is described. Using urea-hydrogen peroxide and phthalic anhydride in ethyl acetate clean conversion into the sulfone was achieved without observation of the possible sulfoxide oxidation product.
Keywords: sulfones; sulfoxides; sulfide oxidation; urea–hydrogen peroxide; UHP; phthalic anhydride